Amelanotic melanoma masquerading as a superficial small round cell tumor: A diagnostic challenge - Archana Shetty; Savitha Anil Kumar; V Geethamani; Mudasser Rehan (Wolters Kluwer Medknow Publications, 2014)
Malignant melanoma poses a remarkable capacity for morphological diversity and often presents as a diagnostic challenge due to its wide clinical presentation. We present a case of a 73-year-old lady, with a large superficial ulcerative nodular mass on the flexor aspect of the right upper arm. On fine needle aspiration poorly differentiated round cell tumor was suggested, with histopathology also supporting the same diagnosis. A final diagnosis of amelanotic melanoma was given following immunohistochemical work-up using a panel of relevant markers. We are presenting this case, not only for its rare clinical presentation, but also for the diagnostic difficulties encountered by us in cytology and histopathology to reach the final diagnosis.